Pan London personalised budgets for rough sleepers. Issue 1 (2014) - ,; ,
Abstract : Purpose – The purpose of this paper is to positively confirm a new and different approach used to engage with entrenched rough sleepers, using the more personalised approach already adopted in social care.Design/methodology/approach – This is a first hand experience of the impact of the approach.Findings – That a personalised approach can achieve positive results with a hard to reach client group.Originality/value – This is the first published paper on this particular project.